Vicious circle: a Joe Pickett novel (Joe Pickett novel, 17,, 2017)
"The Cates family had always been a bad lot. Game warden Joe Pickett had been able to strike a fierce blow against them when the life of his daughter April had been endangered, but he'd always wondered if there'd be a day of reckoning. He's not wondering any longer. Joe knows they're coming after him and his family now. He has his friend Nate by his side, but will that be enough this time? All he can do is prepare -- and wait for them to make the first move." -- Provided by publisher.

Free fire (Joe Pickett novel, 7,, 2008)
Taking advantage of a legal loophole, a lawyer kills four people in Yellowstone National Park and walks away a free man. As the public outcry intensifies, the governor hires former game warden Joe Pickett to conduct a private investigation.

Endangered (Joe Pickett novel, 15,, 2016)
"She was gone. Joe Pickett had good reason to dislike Dallas Cates, even if he was a rodeo champion, and now he has even more--Joe's eighteen-year-old daughter, April, has run off with him. And then comes even worse news: The body of a girl has been found in a ditch along the highway--alive, but just barely, the victim of blunt force trauma. It is April, and the doctors don't know if she'll recover. Cates denies having anything to do with it--says she ran off from him, too--and there's evidence that points to another man. But Joe knows in his gut who's responsible. What he doesn't know is the kind of danger he's about to encounter. Cates is bad enough, but Cates's family is like none Joe has ever met before. Joe's going to find out the truth, even if it kills him. And this time, it just might"--

Storm watch (Joe Pickett novel, 23,, 2023)
"When a prominent University of Wyoming professor goes missing, authorities are stumped. That is, until Joe Pickett makes two surprising discoveries while hunting down a wounded elk on his district as an epic spring storm descends upon him. First, he finds the professor's vehicle parked on a remote mountainside. Then Joe finds the professor's frozen and mutilated body. When he attempts to learn more, his investigation is obstructed by federal agents, extremists, and Governor Colter Allen. Nate Romanowski is rebuilding his falconry company -- and financing this through crypto mining with the assistance of Geronimo Jones. He's then approached by a shadowy group of local militant activists that is gaining in power and influence, and demanding that Wyoming join other western states and secede from the union -- by force, if necessary. They ask Nate to throw in with them, but he's wary. Should he trust them, or is he being set up?" -- Provided by publisher.

Savage run (Joe Pickett novel, 2,, 2003)
Wyoming game warden Joe Pickett uncovers a conspiracy in this explosive novel in the #1 New York Times bestselling series. When a massive blast rocks the forests of Twelve Sleep County, Wyoming game warden Joe Pickett is called to the scene to help investigate the death of a colorful environmental activist. The case is wrapped up quickly, explained as an environmental publicity stunt gone wrong, but Joe isn't convinced. He soon discovers clues that suggest a deadly conspiracy -- one that will test his courage, his survival skills, and his determination to do the right thing despite all costs.

Below zero (Joe Pickett novel, 9,, 2009)
Wyoming game warden Joe Pickett is forced to relive the tragedy of his foster daughter April's apparent death six years earlier when his daughter Sheridan starts receiving text messags from someone claiming to be April. The nightmare rachets up a step when whoever is sending these messages is discovered traveling with suspected environmental terrorists.

Nowhere to run (Joe Pickett novel, 10,, 2010)
Joe Pickett's in his last week as the temporary game warden in the town of Baggs, Wyoming, but there have been strange things going on in the mountains, and his conscience won't let him leave without checking them out: reports of camps looted, tents slashed, elk butchered. And then there's the runner who simply vanished one day.

Out of range: a Joe Pickett novel (Joe Pickett novel, 5,, 2008)
Game warden Joe Pickett is attempting to enjoy - all right, survive - his mother-in-law's wedding to a local big-shot rancher when he receives some disturbing news: Will Jensen, a fellow Wyoming game warden and a good friend, has killed himself. And Joe's been picked to temporarily run Jensen's Teton district. Jackson, Wyoming, is a far cry from Joe's hometown of Saddlestring - it's the epicenter for many environmental extremists and an elite playground for the rich and powerful, and Joe quickly finds himself in over his head. Yet despite the pressures of his new job, he can't get his friend's suicide out of his mind. By all accounts, Will had changed in the last few months, becoming violent and unpredictable.

Open season (Joe Pickett novel, 1,, 2002)
"Joe Pickett is the new game warden in Twelve Sleep, Wyoming, a town where nearly everyone hunts and the game warden -- especially one like Joe who won't take bribes or look the other way -- is far from popular. When he finds a local hunting outfitter dead, splayed out on the woodpile behind his state-owned home, he takes it personally -- and thrusts himself into a mystery that threatens the life and family he loves." -- Provided by publisher.

Breaking point (Joe Pickett novel, 13,, 2013)
Joe Pickett investigates the disappearance of a local businessman, who recently had his intended retirement property declared wetlands and is suspected in the murder of two EPA employees.

Blood trail (Joe Pickett novel, 8,, 2008)
In the wake of an elk hunter's grisly murder, Wyoming game warden Joe Pickett is directed by the governor to investigate the relevance of a mysterious poker chip found at the crime scene.

Winterkill (Joe Pickett novel, 3,, 2016)
"It's an hour away from darkness, a bitter winter storm is raging, and Wyoming Game Warden Joe Pickett is deep in the forest edging Battle Mountain, shotgun in his left hand, his truck's detached steering wheel handcuffed to his right--and an arrow-riddled corpse splayed against the tree in front him. The apparent murder victim and the sudden onslaught of the snowstorm warn: Get off the mountain. But Joe knows this episode is far from over. And when his own daughter gets caught up in his hunt for the killer, Joe will stop at nothing to get her back..."--Back cover.

Trophy hunt (Joe Pickett novel, 04,, 2016)
Local authorities are quick to label a rash of animal mutilations as the work of a grizzly bear, but Joe Pickett suspects that something far more sinister is afoot. When the bodies of two men are found disfigured in the same way, his worst fears are confirmed -- a modern-day Jack the Ripper is on the loose.

In plain sight (Joe Pickett novel, 6,, 2008)
"Ranch owner and matriarch Opal Scarlett has vanished under suspicious circumstances during a bitter struggle between her sons for control of her million-dollar empire. Joe Pickett is convinced one of them have done her in, and when he becomes the victim of a series of wicked and increasingly violent pranks, Joe wonders if what's happening has less to do with Opal's disappearance than with the darkest chapters of his own past. Whoever is after him has a vicious debt to collect, and wants Joe to pay...and pay dearly." -- Page [4] cover.

Cold wind (Joe Pickett novel, 11,, 2011)
When Earl Alden is found dead, dangling from a wind turbine, it's his wife, Missy, who is arrested. Unfortunately for Joe Pickett, Missy is his mother-in- law, a woman he dislikes heartily, and now he doesn't know what to do -- especially when the early signs point to her being guilty as sin. But then things happen to make Joe wonder: Is Earl's death what it appears to be? Is Missy being set up?

Force of nature (Joe Pickett novel, 12,, 2013)
He never wanted to tell Joe Pickett about it, but Nate Romanowski always knew trouble was coming out of his past. Now it's here, and it may not only be the battle of his life-but of Joe's. In 1995, Nate was in a secret Special Forces unit abroad when a colleague did something terrible. Now high up in the government, the man is determined to eliminate anyone who knows about it, and Nate knows exactly how he'll do it-by striking at Nate's friends to draw him out. The entire Pickett family will be a target, and the only way to fight back is outside the law. Nate knows he can do it, but he isn't sure about his straight-arrow friend-and all their lives could depend on it.

Three-inch teeth: a Joe Pickett novel (Joe Pickett novel, 24,, 2024)
"Wyoming game warden Joe Pickett faces two different kinds of rampaging beasts--one animal, one human--in this riveting new novel from #1 New York Times bestseller C.J. Box. A rogue grizzly bear has gone on a rampage--killing, among others, the potential fiancé of Joe's daughter. At the same time, Dallas Cates, who Joe helped lock up years ago, is released from prison with a special list tattooed on his skin. He wants revenge on the people who sent him away: the six people he blames for the deaths of his entire family and the loss of his reputation and property. Using the grizzly attacks as cover, Cates sets out to methodically check off his list. The problem is, both Nate Romanowski and Joe Pickett are on it"--